Interaction between physical activity and problematic mobile phone use on suicidality in Chinese college students - Xie, Yang (BMC Psychiatry, 2020)
BACKGROUND: Previous research has found a relationship between problematic mobile phone use (PMPU) and suicidality. However, few studies have examined the interaction effects between low physical activity (PA) and PMPU on suicidality among college students. This study aimed to examine the interactions of PA and PMPU and their impact on suicidality in a school-based sample among Chinese college students. METHODS: Analysis is based on date from two university in China, which recruited 4787 participants. Binomial logistic regression models were used to explore the associations of PA, PMPU with suicidal ideation and suicide attempt, as well as the interaction of PA and PMPU with suicidality. RESULTS: The prevalence of suicide attempt and suicidal ideation were 3.5 and 7.2%, respectively. Low PA was significantly associated with suicide attempt (OR = 3.48, 95%CI: 2.52–4.81) and suicidal ideation (OR = 1.90, 95%CI: 1.46–2.46). PMPU was significantly associated with suicide attempt (OR = 3.65, 95%CI: 2.66–5.01) and suicidal ideation (OR = 2.83, 95%CI: 2.25–3.54). Interaction analysis indicated that low PA and PMPU were interactively associated with suicide attempt (OR = 9.51, 95%CI: 6.15–14.73, P < 0.001), RERI = 4.85(1.20–8.50), AP = 0.51(0.29–0.73), SI = 2.32(1.34–4.04). There was no additive interaction effects between PA and PMPU on suicidal ideation. CONCLUSIONS: The findings reveals that the intervention programs of suicide attempt should consider the students PA levels and PMPU.